2002
DOI: 10.1128/aem.68.2.1005-1009.2002
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Metabolic Response of Acetogenic Bacteria toward Oxygen

Abstract: The acetogens Sporomusa silvacetica, Moorella thermoacetica, Clostridium magnum, Acetobacterium woodii, and Thermoanaerobacter kivui (i) grew in both semisolid and liquid cultivation media containing O 2 and (ii) consumed small amounts of O 2 . Low concentrations of O 2 caused a lag phase in growth but did not alter the ability of these acetogens to synthesize acetate via the acetyl coenzyme A pathway. Cell extracts of S. silvacetica, M. thermoacetica, and C. magnum contained peroxidase and NADH oxidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 20 publications
2
78
0
1
Order By: Relevance
“…H 2 -CO 2 , formate, methanol and a few other compounds serve as substrates, and acetate is the sole reduced end product. C. magnum can assimilate N 2 (Bomar et al, 1991) and tolerate and consume small amounts of O 2 (Karnholz et al, 2002). Growth is possible at 15-45 1C with the optimum at 30-32 1C.…”
Section: T-rf (Bp)mentioning
confidence: 99%
“…H 2 -CO 2 , formate, methanol and a few other compounds serve as substrates, and acetate is the sole reduced end product. C. magnum can assimilate N 2 (Bomar et al, 1991) and tolerate and consume small amounts of O 2 (Karnholz et al, 2002). Growth is possible at 15-45 1C with the optimum at 30-32 1C.…”
Section: T-rf (Bp)mentioning
confidence: 99%
“…Kawasaki et al found that the peptide transcripts of A-type flavoprotein homologue and novel type rubrerythrin homologue in C. acetobutylicum were upregulated within ten minutes of an oxygen shock [246]. Other enzymes thought to be involved in oxygen metabolism in acetogens include NADH-oxidase, superoxide dismutase, and rubrerythrin [244,247]. Karnholz et al found that acetogens including M. thermoacetica and A. woodii grew in non-reduced liquid medium containing small amounts of O 2 gas; furthermore, they found that increasing this amount of O 2 caused an increase in the lag growth phase, with a decrease in final biomass achieved [244].…”
Section: Gasification and Gas Clean-upmentioning
confidence: 99%
“…For example, pyruvate-ferredoxin oxidoreductase catalyses a pyruvate-CO 2 exchange reaction: its exposed iron-sulphur sites are susceptible to oxidative inactivation, leading it to be one of the most oxygen sensitive enzymes known [121,242,243]. Interestingly, some acetogens have an oxygen detoxification pathway which allows them to tolerate certain levels of oxidative stress [244]. This has been demonstrated physiologically throughout the Clostridium genus, with species such as Clostridium butyricum and C. acetobutylicum being shown to resume growth following oxygen consumption, with no lasting damage.…”
Section: Gasification and Gas Clean-upmentioning
confidence: 99%
“…In contrast, C. thermocellum (IAM 13660 T ) could not grow in an atmosphere containing an O 2 concentration of more than 2 %. In the genus Clostridium, some species that can grow in an atmosphere containing an O 2 concentration of up to 6 % have been reported, and the species have the ability to consume O 2 (Küsel et al, 2001;Karnholz et al, 2002). Colour changing of resazurin in the media indicated that strain CSK1 T consumes O 2 during cultivation in an atmosphere containing O 2 .…”
mentioning
confidence: 99%